Distribution and species identification in the crustacean isopod genus Dynamene Leach, 1814 along the North East Atlantic-Black Sea axis - Vieira, Pedro E. (2016)
Sphaeromatid isopods, such as Dynamene, are common and abundant members of the invertebrate fauna of littoral and shallow sublittoral substrates. Six species of Dynamene occur in the northern hemisphere. Only two species exist outside this range, in Australia. The distribution of the various species in the NE Atlantic-Black Sea axis has been controversial due to the difficulty in the identification of the different species. This has led to inaccurate records of their distribution, ultimately generating uncertain or faulty assessments on the biodiversity of these habitats. An update and a clarification about the distribution of this genus is therefore in order. In this study, we describe the distribution of Dynamene species in the light of new records from the NE Atlantic Ocean and its associated islands, and the Mediterranean, Black and Red Seas, and from re-examination of museum and several authors' personal collections. Based on these observations, we extend the northern and southern limits of Dynamene bidentata (Adams); the western and southern limits of Dynamene magnitorata Holdich; the northern, eastern and western limits of Dynamene edwardsi (Lucas); and the eastern and western limits of Dynamene bifida Torelli. The range of Dynamene tubicauda Holdich is extended, but is still only known from the eastern Mediterranean. We also clarify the synonymy of Dynamene torelliae Holdich with Dynamene bicolor (Rathke), and the occurrence of Dynamene bicolor in the Black Sea. New distribution maps of the six Dynamene species are presented. Illustrated keys to the adult males and females of the northern hemisphere species are provided.